Lights and scientific modernities diffusion: an analysis of the metalinguistics of the 19th century scientific dissemination discourse - Cavalcante Filho, Urbano (Redis: Revista de Estudos do Discurso, 2015)
This paper aims to present an analysis of the scientific dissemination discourse in the 19th century in Brazil. For such, we seek basis on the theoretical reflections that come from Bakhtin’s Circle in order to analyze one of the most meaningful scientific knowledges dissemination in Brazil in the eighteenth century: Glória’s Popular Conferences. Two major axes guide this study: 1) the analysis of the discourse genre conference, since this genre is one of Brazil’s scientific dissemination discourse materialization places of the nineteenth century, in order to realize how this utterance reflects and portrays certain conditions and coertions of specific communication fields, considering their constituent elements (thematic content, style and compositional form); 2) based on the bakhtinian metalinguistics show how the scientific dissemination utterance establishes dialogic-semantic relations with utterances from other ideological spheres, having as an example the scientific, philosophical and religious utterances in circulation in a sociodiscursive context of the nineteenth century.